The Concept Of Enemy Combatant By United States: Does International Humanitarian Law Recognized This Concept? (Case Study: Armed Conflict Between United States, Al Qaeda And Taliban) - Adhitya Nini Rizki Apriliana; Lina Hastuti (Fakultas Hukum Universitas Mataram, 2019)
International humanitarian law recognized the classification of population during the war, namely: combatant; hors de combat; non-combatant; and civilians. Civilians is the parties who should be protected from enemy attacks and conversely this classification should not be attacked under any circumstances. In the other side of these classifications, the United States arrested around 200 Afghan children and teenagers on charges of being enemy combatant and detained them at the Detention Facility in Parwan. The act taken by the United States is not recognized in international humanitarian law since terms enemy combatant is not suitable with any other terms in international humanitarian law. The United States arrested children who did not took up arms and were not involved in the war but ‘allegedly’ involved with terrorist networks and were considered to treated state security. Phrase ‘allegedly’ refers to subjectivity and hard to describe. This research will discuss how international humanitarian law deal with the United States new terms namely enemy combatant. This study uses statutory approach which examining the laws and regulations concerned with the formulation of the problem discussed. It also uses conceptual approach which moves from the views and doctrines that develop in law to build a legal concept. This study is purpose to analyze legal basis and principles of international customary law related to the concept of enemy combatant as applied unilaterally by the United States to the armed conflict in Afghanistan.